PENGARUH PARTISIPASI ANGGARAN, ASIMETRI INFORMASI, KAPASITAS INDIVIDU, DAN KEJELASAN SASARAN ANGGARAN TERHADAP POTENSI TERJADINYA BUDGETARY SLACK - Tresnayani, Luh Gede Ardi; Gayatri, ' (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of budget participation, information asymmetry, the capacity of individuals, and the clarity of the budget targets for potential budgetary slack. This research was conducted at the regional work units Bangli regency. The population in this study are all SKPD Bangli. The sample in this study using purposive sampling method with a sample of 108 respondents. This study uses data collection using questionnaires. The analysis technique used is multiple linear regression. Results of this analysis indicate budget participation and budget goal clarity negatively affect the potential budgetary slack. Instead the results of the analysis of asymmetry of information and the capacity of individuals showed a positive relationship to the potential budgetary slack.
Keywords: budget, information asymmetry, budgetary slack